Analisis Implementasi SAK EMKM Pada Tahun Penyajian Laporan Keuangan Kepada Umkm Di Desa Gunung Baringin Padang Lawas - Hamidah Sari; Laylan Syafina; Nurwani Nurwani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the preparation of MSME financial reports in Gunung Baringin Village, and the application of SAK EMKM in presenting financial reports in MSMEs and knowing the obstacles in preparing financial reports based on SAK EMKM. This research uses a qualitative descriptive method and the data in this study were obtained through interviews with MSME actors, documentation and literature studies. The research subjects were MSME owners in Gunung Baringin Padang Lawas Village, namely MSME Sayur Mayur, Mhd Irsyad and MSME Baginda Raja Jaya. The results of data analysis show that MSMEs in Gunung Baringin Village have not implemented SAK-EMKM in their financial reports, and the recording carried out is still simple, namely only recording total income and expenses. The presentation of MSME financial reports in accordance with SAK EMKM includes profit and loss statements, statements of financial position and CALK (Notes to Financial Statements). The main obstacles faced by MSME actors in implementing SAK-EMKM are the lack of adequate human resources, the lack of understanding of MSME actors regarding accounting knowledge, and the absence of MSME actors who have an accounting education background.